Catalyst with porous heat-conducting core-shell structure, preparation method and application
By using the porous thermal core-shell structure of Cu-La2O3-Al@Cu-La2O3 catalyst, the problems of high cost, low selectivity and insufficient production capacity when converting aromatic aldehydes into aromatic alcohols are solved, and high conversion rate and selectivity are achieved, which is suitable for production of ten thousand tons.
Patent Information
- Application Number
- CN202411851008.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art has problems of high catalyst cost, low selectivity and insufficient production capacity when converting aromatic aldehydes into aromatic alcohols on a large scale. Especially in fixed bed reactors, the condensation of aromatic aldehydes and alcohol solvents to form acetals, resulting in catalyst deactivation and bed blockage.
Cu-La2O3-Al@Cu-La2O3 catalyst is used, which has a porous thermal conductivity core-shell structure. By using Cu-La2O3 as the shell and Al as the core, it provides thermal conductivity and rich mesoporous channels, which improves raw material diffusion and catalyst life.
The high conversion and selectivity of aromatic alcohols are achieved by selective hydrogenation of aromatic aldehydes, the catalyst is low in cost, suitable for production of ten thousand tons, and the service life of the catalyst is extended.
Smart Images

Figure CN119793475A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalytic conversion, and in particular to a catalyst with a porous heat-conducting core-shell structure, a preparation method and an application thereof. Background Art
[0002] As an important organic intermediate and chemical raw material, benzaldehyde is widely used in the fields of food, medicine and fine chemicals. In industry, benzaldehyde is mainly prepared by hydrolysis using the benzyl chloride method, but this method has many disadvantages such as complex operation, low yield and serious environmental pollution, which does not meet the requirements of green chemistry and economic sustainable development. In addition, due to the characteristics of the process itself, the benzaldehyde produced by the benzyl chloride method contains chlorine, which does not meet the standards of the food and drug industry.
[0003] The process of generating benzyl alcohol by hydrogenation of benzaldehyde as raw material has a wide range of benzyl alcohol raw materials, which can be prepared by hydrogenation of methyl benzoate or benzoic acid, and the product does not contain chlorine to meet the requirements of spices and pharmaceutical products, and the process and operation flow are simple, environmentally friendly, high yield of benzyl alcohol, good atom economy, and more advantageous than traditional methods. Publication number CN1686989A discloses a method of synthesizing benzyl alcohol by temperature gradient, adopts temperature gradient reactor, takes methyl benzoate as raw material, adopts Mn and Cu catalyst one-step method to realize the synthesis of benzyl alcohol, but the selectivity of benzyl alcohol is low, only 60~80%. Publication number CN110724032A discloses a method of preparing alcohol compounds by hydrogenation reduction of ketone and aldehyde, ketone / aldehyde compounds are efficiently catalyzed by nanoporous palladium catalyst, and the reaction conditions are mild, but it is suitable for small-scale high value-added products, and it is not suitable for 10,000-ton scale production, and the catalyst is expensive, and the catalyst recovery and repeated use are cumbersome. Reference 1 (Yan Feng, et al. Effect of the degree of dispersion of Pt over MgAl2O4 on the catalytic hydrogenation of benzaldehyde. Chinese Journal of Catalysis, 2017, 38 1613-1620, doi: 10.1016 / S1872-2067(17)62815-8) reported that Pt / MgAl2O4 spinel catalyst was used for the hydrogenation of benzaldehyde in liquid phase (tank reactor) to prepare benzyl alcohol. The yield of benzyl alcohol could reach 99.4%, and no obvious deactivation was observed after six cycles of the catalyst. Reference 2 (Zhou Fang, et al. Benzaldehyde Hydrogenation Performance of Pd Catalysts Supported by Different Supports, 2013, 42, 606-609, doi:10.16581 / j.cnki.issn1671-3206.2013.04.006) used SiC, MgO, Si3N4 and high-temperature deoxygenated activated carbon supported Pd catalysts to hydrogenate liquid benzaldehyde (BAL) to produce benzyl alcohol. The results show that when the conversion rate is 80%, the benzyl alcohol yield is nearly 100%, but as the conversion rate increases further, the benzyl alcohol selectivity begins to decrease significantly.
[0004] Therefore, by using aromatic aldehydes as raw materials to produce aromatic alcohols on a large scale, the current research status at home and abroad shows that there are the following problems:
[0005] (1) In order to increase the production capacity of aromatic alcohols by hydrogenating aromatic aldehydes on a large scale, fixed bed reactors are more suitable for actual needs than tank reactors;
[0006] (2) Aromatic aldehydes and alcohol solvents are adsorbed on the surface of the carrier and condensed to form acetals. The fixed bed shortens the residence time of the methanol product on the catalyst and reduces the formation of acetals.
[0007] (3) Precious metals are expensive, so the development of non-precious metal hydrogenation catalysts is more meaningful. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a catalyst with a porous heat-conducting core-shell structure, which has a core-shell structure with Cu-La2O3 as the shell and Cu-La2O3-Al as the core, and can selectively catalyze the conversion of aromatic aldehydes into aromatic alcohols with a selectivity of up to 95%.
[0009] A catalyst with a porous heat-conducting core-shell structure, wherein the core-shell structure has Cu-La2O3 as a shell and Cu-La2O3-Al as a core.
[0010] The catalyst in the present invention (i.e., Cu-La2O3-Al@Cu-La2O3, referred to as core@shell) has a core-shell structure with Cu-La2O3 as the shell and Cu-La2O3-Al as the core, providing an Al core with good thermal conductivity, which can quickly remove the heat from the bed layer and prevent the catalyst surface temperature from being too high, resulting in sintering and deactivation. At the same time, the metal aluminum in the core serves as a catalyst skeleton; La2O3 as an auxiliary agent can not only improve the life of the catalyst, but its oxygen vacancies enhance the adsorption capacity of the raw materials; copper is the active component of the aromatic aldehyde hydrogenation catalyst, and also has the effect of rapid heat removal during the reaction. The catalyst has a Cu-La2O3 structure with abundant mesoporous channels as a shell, which is conducive to the diffusion of raw materials, prevents the occurrence of aromatic aldehyde polymerization reaction, solves the problem of aromatic aldehyde condensing with alcohol solvents to generate acetal byproducts, causing bed blockage, and improves the service life of the catalyst.
[0011] Preferably, in the catalyst having a porous heat-conducting core-shell structure, the mass ratio of Cu, Al and La is (5-50):(1-30):(25-50).
[0012] In the present invention, when the mass ratio of Cu, Al and La is within the above range, the conversion rate of the catalyst for selective hydrogenation of aromatic aldehydes to prepare aromatic alcohols is as high as 96%, wherein the selectivity of benzyl alcohol is as high as 95%.
[0013] The present invention also provides a method for preparing the catalyst having a porous thermal conductive core-shell structure. The catalyst having a porous thermal conductive core-shell structure is prepared by a melting-corrosion method. The preparation process is as follows: Figure 1 As shown, the synthesis is simple and easy to scale up.
[0014] A method for preparing a catalyst having a porous heat-conducting core-shell structure comprises the following steps:
[0015] (1) mixing copper powder, aluminum powder and La2O3 according to a mass ratio and then calcining to obtain a Cu-La2O3-Al alloy;
[0016] (2) placing the Cu-La2O3-Al alloy obtained in step (1) in a sodium hydroxide solution for corrosion reaction to obtain a catalyst having a porous thermal conductive core-shell structure.
[0017] In the present invention, copper powder, aluminum powder and La2O3 are mixed and then roasted to obtain a Cu-La2O3-Al alloy, and sodium hydroxide is used to corrode the Cu-La2O3-Al alloy. Aluminum, as an amphoteric substance, can reflect both the acidity of non-metals and the reducing properties of metals, and can react with sodium hydroxide to generate sodium tetrahydroxyaluminate. The reaction equation is as follows:
[0018] 2Al+2NaOH+6H2O→2Na[Al(OH)4]+3H2,
[0019] Therefore, the Al on the surface of the Cu-La2O3-Al alloy will be corroded by the sodium hydroxide solution to form a core-shell structure with multiple mesopores, namely, the Cu-La2O3-Al@Cu-La2O3 catalyst. The presence of mesopores is conducive to the diffusion of raw materials during the catalytic reaction and prevents the occurrence of aldehyde polymerization.
[0020] Preferably, the calcination temperature is 1000-2300°C.
[0021] Preferably, the concentration of the sodium hydroxide solution is 5-10 mol / L.
[0022] Preferably, the temperature of the corrosion reaction is 60-100° C., and the time of the corrosion reaction is 1-12 hours.
[0023] In the present invention, the depth of the Cu-La2O3 shell in the catalyst is controlled by controlling the temperature and time of the corrosion reaction. As the corrosion temperature increases and the corrosion time prolongs, the thickness of the shell in the catalyst gradually increases.
[0024] The present invention also provides the use of the catalyst having a porous heat-conducting core-shell structure in the selective hydrogenation of aromatic aldehydes to prepare aromatic alcohols, especially for the hydrogenation of methyl benzoate to prepare benzyl alcohol. The conversion rate of the Cu-La2O3-Al@Cu-La2O3 catalyst in the selective hydrogenation of methyl benzoate to prepare aromatic benzyl alcohol is greater than 96%, and the selectivity of benzyl alcohol is greater than 95%.
[0025] Preferably, the method for using the catalyst with a porous heat-conducting core-shell structure in the selective hydrogenation of aromatic aldehydes to prepare aromatic alcohols is as follows: first, the catalyst with a porous heat-conducting core-shell structure is filled into a continuous fixed bed reactor, the catalyst is reduced with hydrogen, cooled to the reaction temperature, aromatic aldehydes are added, and hydrogenation reaction is continued in hydrogen to obtain aromatic alcohols.
[0026] More preferably, the hydrogen reduction temperature is 200-400°C.
[0027] More preferably, the hydrogen concentration is 10% to 100%.
[0028] More preferably, the reaction temperature of the selective hydrogenation of aromatic aldehydes is 100-250°C, the hydrogen-aldehyde ratio is 10-100:1, and the space velocity is 0.1-1.0h -1 .
[0029] In the present invention, the hydrogen-to-formaldehyde ratio is the molar ratio of hydrogen to aromatic aldehyde, and the space velocity is the amount of gas treated by a unit volume of catalyst per unit time. When the hydrogen-to-formaldehyde ratio and the space velocity are within the above range, the conversion rate of the catalytic reaction can be maintained at a relatively high level.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The present invention provides a Cu-La2O3-Al@Cu-La2O3 catalyst, which provides an Al core with good thermal conductivity, which can quickly remove the heat from the bed layer and prevent the catalyst surface temperature from being too high, resulting in sintering and deactivation. At the same time, the catalyst has a rich mesoporous Cu-La2O3 structure as a shell, which is conducive to the diffusion of raw materials and prevents the occurrence of aromatic aldehyde polymerization.
[0032] (2) The catalyst provided by the present invention uses non-precious metal elements Cu, Al, and La, and the cost of the catalyst is low.
[0033] (3) The present invention adopts a melt-corrosion method to prepare a catalyst having a porous thermal conductive core-shell structure, and the synthesis operation is simple and easy to scale up on a large scale.
[0034] (4) The catalyst with a porous heat-conducting core-shell structure provided by the present invention can be used for the selective hydrogenation of aromatic aldehydes to prepare aromatic alcohols. The reaction is carried out in a continuous fixed-bed reactor. It has the advantages of simple synthesis, low cost, and high selectivity for aromatic aldehydes, and can be applied on a large scale in a 10,000-ton aromatic aldehyde project. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a flow chart for preparing catalysts having a porous thermally conductive core-shell structure according to Examples 1 to 4. DETAILED DESCRIPTION
[0036] The present invention will be further described in detail below in conjunction with the examples, but the embodiments of the present invention are not limited to the following examples.
[0037] The raw materials used in the present invention are all commercially available.
[0038] Example 1: Preparation process as follows Figure 1 shown.
[0039] (1) Copper powder, aluminum powder and La2O3 are uniformly mixed according to a mass ratio of Cu, Al and La of 45:10:45, and then heated at 1500°C in a nitrogen atmosphere. After cooling, the powder is taken out, formed, tableted and sieved to a particle size of 20 to 40 meshes to obtain a Cu-La2O3-Al alloy;
[0040] (2) The Cu-La2O3-Al alloy obtained in step (1) was immersed in a 5 mol / L NaOH solution, vigorously stirred at 80°C for 1 h, and repeatedly washed with deionized water until the pH value was 7. After drying at 120°C and calcining with nitrogen at 500°C, the catalyst was formed, tableted, and sieved to a particle size of 20 to 40 meshes to obtain a catalyst with a porous thermal conductive core-shell structure, i.e., Cu-La2O3-Al@Cu-La2O3 catalyst.
[0041] Example 2
[0042] The preparation method is the same as that of Example 1, except that the mass ratio of Cu, Al and La is 40:20:40.
[0043] Example 3
[0044] The preparation method is the same as that of Example 1, except that the mass ratio of Cu, Al and La is 47:6:47.
[0045] Example 4
[0046] The preparation method is the same as that of Example 1, except that the mass ratio of Cu, Al and La is 30:10:60.
[0047] Comparative Example 1
[0048] The industrial Cu-Zn-Al catalyst was purchased from Qingdao Xunneng New Material Technology Co., Ltd. with the product number D308G-1, in which the mass ratio of Cu, Zn and Al was 45:45:10.
[0049] Comparative Example 2
[0050] Industrial Cu-SiO2 catalyst was purchased from Qingdao Xunneng New Material Technology Co., Ltd. with the product number FA-G-1, in which the mass ratio of Cu to Si was 45:45.
[0051] Comparative Example 3
[0052] Copper powder and La2O3 were evenly mixed according to the mass ratio of Cu to La of 50:50, and then heated at 1500°C in a nitrogen atmosphere. After cooling, the powder was taken out, formed, tableted, and sieved to a particle size of 20-40 mesh to obtain a Cu-La2O3 catalyst.
[0053] Comparative Example 4
[0054] Copper powder, aluminum powder and La2O3 were evenly mixed according to the mass ratio of Cu, Al and La of 45:10:45, and then heated at 1500°C in a nitrogen atmosphere. After cooling, the powder was taken out, formed, tableted and sieved to a particle size of 20 to 40 mesh to obtain a Cu-La2O3-Al catalyst.
[0055] Sample analysis
[0056] The catalysts of Examples 1 to 4 and Comparative Examples 1 to 4 were used to catalyze the reaction of selective hydrogenation of methyl benzoate to obtain benzyl alcohol. The specific reaction process was as follows: First, each group of catalysts was filled into a continuous fixed bed reactor, and the catalyst was reduced with 100% hydrogen at 250° C. for 5 h, then cooled to a reaction temperature of 120° C., and methyl benzoate was pumped into the reactor using a high-pressure pump and continued to be hydrogenated in hydrogen to obtain benzyl alcohol, wherein the hydrogen-to-aldehyde ratio was 20:1 and the space velocity was 0.2 h -1 After calculation, the conversion rate, benzyl alcohol selectivity and toluene selectivity were obtained, and the results are shown in the following table.
[0057] Table 1: Conversion rate, benzyl alcohol selectivity and toluene selectivity of the catalysts of Examples 1 to 4 and Comparative Examples 1 to 4 in catalytic hydrogenation reactions
[0058]
[0059] As shown in Table 1, the conversion rate of the Cu-La2O3-Al@Cu-La2O3 catalyst provided by the present invention is >96%, the benzyl alcohol selectivity is >95%, and the toluene selectivity is <2%, which are significantly better than those of the comparative examples.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A catalyst having a porous heat-conducting core-shell structure, characterized in that: The core-shell structure has Cu-La2O3 as the shell and Cu-La2O3-Al as the core.
2. The catalyst having a porous heat-conducting core-shell structure according to claim 1, characterized in that: The mass ratio of Cu, Al and La is (5-50):(1-30):(25-50).
3. The method for preparing a catalyst having a porous heat-conducting core-shell structure according to claim 1 or 2, characterized in that: The following steps are involved: (1) mixing copper powder, aluminum powder and La2O3 according to a mass ratio and then calcining to obtain a Cu-La2O3-Al alloy; (2) placing the Cu-La2O3-Al alloy obtained in step (1) in a sodium hydroxide solution for corrosion reaction to obtain a catalyst having a porous thermal conductive core-shell structure.
4. The method for preparing a catalyst having a porous thermally conductive core-shell structure according to claim 3, characterized in that: The calcination temperature is 1000-2300°C.
5. The method for preparing a catalyst having a porous heat-conducting core-shell structure according to claim 3, characterized in that: The concentration of the sodium hydroxide solution is 5-10 mol / L.
6. The method for preparing a catalyst having a porous heat-conducting core-shell structure according to claim 3, characterized in that: The temperature of the corrosion reaction is 60-100° C., and the time of the corrosion reaction is 1-12 hours.
7. Use of the catalyst having a porous heat-conducting core-shell structure according to claim 1 or 2 in the reaction of selective hydrogenation of aromatic aldehydes to prepare aromatic alcohols.
8. The use according to claim 7, characterized in that: The method for using the catalyst with a porous heat-conducting core-shell structure in the selective hydrogenation reaction of aromatic aldehydes to prepare aromatic alcohols comprises the following steps: firstly, the catalyst with a porous heat-conducting core-shell structure is filled into a continuous fixed bed reactor, the catalyst is reduced with hydrogen, the temperature is lowered to the reaction temperature, aromatic aldehyde is added and the hydrogenation reaction is continued in hydrogen to prepare aromatic alcohols.
9. The use according to claim 8, wherein the hydrogen reduction temperature is 200-400°C, and the hydrogen concentration is 10%-100%.
10. The use according to claim 8, characterized in that: The temperature of the hydrogenation reaction is 100-250°C, the hydrogen-formaldehyde ratio is 10-100:1, and the space velocity is 0.1-1.0h -1 .
Citation Information
Patent Citations
Method for preparing alcohol compounds through hydrogenation reduction of ketone and aldehyde
CN110724032A
Method for synthesizing benzoic alcohol by using temperature gradient
CN1686989A